The equine nurse's approach to arthroscopic surgery: part 1 – equipment & instrumentation. Issue 9 (16th November 2020) - Ryan, Jackie; Johnson, Jessica P.
ABSTRACT: The equine veterinary nurse plays a crucial role in the purchase, maintenance, sterilisation and set-up of arthroscopic equipment and instrumentation. This three-part review will cover all of these aspects, and aims to serve as a practical resource for the equine surgical nurse. In Part 1, we will provide a brief introduction to the equipment and instrumentation required for arthroscopic surgery in horses.